Shakespeare''s Theatre : a Dictionary of His Stage Context. - Richmond, Hugh Macrae (Continuum Shakespeare Dictionaries., 2003)
Shakespeare''s Theatre consolidates the author''s forty years of experience in studying and staging Shakespeare''s plays. Under an alphabetical list of relevant terms, names and concepts, the book reviews current knowledge of the character and operation of theatres in Shakespeare''s time, with an explanation of their origins. Coverage includes the practices of Elizabethan actors and script writers: methods of characterization; gesture, blocking and choreography, including music, dance and fighting; actors'' rhetorical interaction with audiences; and use of costumes, stage props, and make-up. T.